2021
DOI: 10.15587/2519-4798.2021.238093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and morphological comparison of respiratory failure in patients with COVID-19 who died under different options of respiratory support

Abstract: The aim. Based on the study of the effect of invasive mechanical ventilation and NIV in the CPAP mode on the pathomorphosis of lung damage in patients with HRF caused by SARS-nCoV-2 and deaths in intensive care unit (ICU), determine the safest method of respiratory support. Materials and methods. The study included morphological material from 20 patients with HRF caused by SARS-nCoV-2 (COVID-19) who died in ICU. Group 1 included patients who received non-invasive lung ventilation in CPAP mode through a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is known that a significant amount of virus detected in the respiratory tract exacerbates diffuse alveolar damage and airway obstruction associated with impaired ventilation, which supports the cytotoxic effect of SARS-CoV-2 and causes respiratory failure, and a decrease in viral RNA is characteristic of the course of the disease with morphological manifestations of reduced lung epithelial cell proliferation and the formation of severe pulmonary fibrosis [11] . Of interest for comparison are the data of V. Skoryk et al, according to which scientists have shown the effect of long-term respiratory support on accelerating the development of irreversible processes in the lungs, namely the development of pneumofibrosis and complications due to the accession of ventilation-associated pneumonia [12] barotrauma in patients with COVID-19 due to the coexistence of severely affected areas of the lungs adjacent to relatively unaffected areas. Affected areas with atelectasis cannot or are very difficult to straighten by selecting ventilation parameters or increasing the pressure at the end of exhalation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a significant amount of virus detected in the respiratory tract exacerbates diffuse alveolar damage and airway obstruction associated with impaired ventilation, which supports the cytotoxic effect of SARS-CoV-2 and causes respiratory failure, and a decrease in viral RNA is characteristic of the course of the disease with morphological manifestations of reduced lung epithelial cell proliferation and the formation of severe pulmonary fibrosis [11] . Of interest for comparison are the data of V. Skoryk et al, according to which scientists have shown the effect of long-term respiratory support on accelerating the development of irreversible processes in the lungs, namely the development of pneumofibrosis and complications due to the accession of ventilation-associated pneumonia [12] barotrauma in patients with COVID-19 due to the coexistence of severely affected areas of the lungs adjacent to relatively unaffected areas. Affected areas with atelectasis cannot or are very difficult to straighten by selecting ventilation parameters or increasing the pressure at the end of exhalation.…”
Section: Discussionmentioning
confidence: 99%